Glucagon-like peptide-1 derived cardioprotection does not utilize a KATP-channel dependent pathway: mechanistic insights from human supply and demand ischemia studies. Issue 1 (December 2016) - Giblett, Joel; Axell, Richard; White, Paul; Clarke, Sophie; McCormick, Liam; Read, Philip; Reinhold, Johannes; Brown, Adam; O'Sullivan, Michael; West, Nick; Dutka, David; Hoole, Stephen
Abstract Background Glucagon-like peptide-1 (7–36) amide (GLP-1) protects against stunning and cumulative left ventricular dysfunction in humans. The mechanism remains uncertain but GLP-1 may act by opening mitochondrial K-ATP channels in a similar fashion to ischemic conditioning. We investigated whether blockade of K-ATP channels with glibenclamide abrogated the protective effect of GLP-1 in humans. Methods Thirty-two non-diabetic patients awaiting stenting of the left anterior descending artery (LAD) were allocated into 4 groups (control, glibenclamide, GLP-1, and GLP-1 + glibenclamide). Glibenclamide was given orally prior to the procedure. A left ventricular conductance catheter recorded pressure–volume loops during a 1-min low-pressure balloon occlusion (BO1) of the LAD. GLP-1 or saline was then infused for 30-min followed by a further 1-min balloon occlusion (BO2). In a non-invasive study, 10 non-diabetic patients were randomized to receive two dobutamine stress echocardiograms (DSE) during GLP-1 infusion with or without oral glibenclamide pretreatment. Results GLP-1 prevented stunning even with glibenclamide pretreatment; the Δ % dP/dtmax 30-min post-BO1 normalized to baseline after GLP-1: 0.3 ± 6.8 % (p = 0.02) and GLP-1 + glibenclamide: −0.8 ± 9.0 % (p = 0.04) compared to control: −11.5 ± 10.0 %. GLP-1 also reduced cumulative stunning after BO2: −12.8 ± 10.5 % (p = 0.02) as did GLP-1 + glibenclamide: −14.9 ± 9.2 % (p = 0.02) compared to control: −25.7 ± 9.6 %. Glibenclamide alone was no different to control. Glibenclamide pretreatment did not affect global or regional systolic function after GLP-1 at peak DSE stress (EF 74.6 ± 6.4 vs. 74.0 ± 8.0, p = 0.76) or recovery (EF 61.9 ± 5.7 vs. 61.4 ± 5.6, p = 0.74). Conclusions Glibenclamide pretreatment does not abrogate the protective effect of GLP-1 in human models of non-lethal myocardial ischemia. Trial registration Clinicaltrials.gov Unique Identifier: NCT02128022